Prevalence of risk factors for noncommunicable diseases among rural women in Yemen. Issue 2 (1st May 2018) - Alwabr, Gawad M.A.
Abstract : Objective: The objective of this study was to expand the evidence base on the prevalence of risk factors for the main noncommunicable diseases (such as diabetes mellitus, blood pressure, and obesity) among rural women in Yemen. Methods: A descriptive cross-sectional study was conducted among 450 rural women in the age range from 18 to 60 years who presented in the targeted health centers of Sana'a and Al-Mahweet governorates during the time of the study. Data were collected by a structured questionnaire developed as per World Health Organization STEPS guidelines. Body mass index, blood pressure, and biochemical measurements of fasting blood glucose were recorded. Results: Ninety-four percent of the respondents were physically inactive. Only 3.5% of respondents were smokers, while 66.3% were qat chewers. Forty-seven percent watched TV. Thirty-nine percent of respondents ate vegetables daily, while 19.5% consumed fruits daily. Among the respondents, 31.3% were obese, 15.0% were hypertensive, and 7.8% had diabetes mellitus. Age group, marital status, and education level were significantly associated with obesity, blood pressure, and diabetes mellitus. There were significant associations between obesity and blood pressure, as well as between blood pressure and diabetes mellitus. Conclusion: Frequent campaigns and educational programs are to be encouraged for the adoption of healthy lifestyle practices and health promotion. Significance statement: Noncommunicable diseases (NCDs) morbidity and death are increasing rapidly, particularly among developing countries, including Yemen. Information on risk factors predicts the future burden of diseases. The results of this study will complement the limited knowledge of the existing interactions between sociodemographic characteristics, behavior, and noncommunicable diseases among rural women in Yemen. It will also be a fundamental starting point for health planning and execution of health promotion interventions.